Near room temperature dielectric transition in the perovskite formate framework [(CH(3))(2)NH(2)][Mg(HCOO)(3)]. - Pato-Doldán, B; Sánchez-Andújar, M; Gómez-Aguirre, L; Yáñez-Vilar, S; López-Beceiro, J; Gracia-Fernández, C; Haghighirad, A; Ritter, F; Castro-García, S; Señarís-Rodríguez, M (2012)
We report that the hybrid organic-inorganic compound [(CH(3))(2)NH(2)][Mg(HCOO)(3)] shows a marked dielectric transition around T(t) ∼ 270 K, associated to a structural phase transition from SG R3[combining macron]c (centrosymmetric) to Cc (non-centrosymmetric). This is the highest T(t) reported so far for a perovskite-like formate that is thus a promising candidate to display electric order very close to room temperature.